Teachers’ Strategies to Implement Higher-Order Thinking Skills in English Instruction - Christian Bernard Nichols Djami; Paulus Kuswandono (Metathesis: Journal of English Language, Literature, and Teaching, 2020)
This study investigated English teachers’ strategies to implement HOTS (Higher-Order Thinking Skills) during the learning process. To prepare students for education 4.0, Indonesian government has mandated that HOTS are taught in every level of education. The research aimed to discover how English teachers implemented HOTS in their teaching strategies. HOTS are promoted in the 2013 curriculum in which English teachers should develop their strategies to implement these skills through student-centered learning instead of teacher-centered learning that may be a common phenomenon for teachers in Indonesia. The participants of the study were fifteen senior high school English teachers in Salatiga, and five of whom were interviewed and observed. The data were obtained through questionnaire, interview, and observation. The data analysis involved counting the percentage for the questionnaire and reading collected transcripts from the interviews and the observation notes. The data analysis was processed using descriptive statistics for the questionnaire and coding for eliciting the transcripts and observation notes. The results of the study showed that the effective teaching strategies in using HOTS were asking open-ended questions and encouraging students to give their critical opinion, while also acting as a facilitator.